The Implementation and Integration of Merdeka Curriculum and STEM at All Levels of Education - Christina Ester Manthalina Hutabarat; Yuanita Puspita Dewi Sudarso (Didaktika: Jurnal Kependidikan, 2026)
Indonesia’s new educational curriculum, Merdeka Curriculum, has successfully integrated the Independent Curriculum and STEM education. The primary objective of this integration is to enhance the learning experience for students at the elementary, junior high, and high school levels by providing them with better facilities and developing the competencies of both teachers and students. The STEM-based curriculum utilizes project-based learning to make education more relevant and contextual, with teachers acting as facilitators. To determine the effectiveness of this curriculum and its integration with STEM in classrooms, an analysis is required. This study aims to identify the barriers and challenges teachers face in implementing the Merdeka Curriculum and STEM, the consequences of this integration, and the readiness of teachers to apply models or approaches to organize it.